PEMBERDAYAAN MASYARAKAT PERDESAAN BERBASIS AGROINDUSTRI PANGAN LOKAL (Suatu Kajian Agroindustri Gula Kelapa Kristal di Kecamatan Kokap Kabupaten Kulon Progo Propinsi Daerah Istimewa Yogyakarta) - VINI ARUMSARI; SITI SYAMSIAR (Universitas Sebelas Maret, 2011)
The Agroindustry of local food in rural areas is an activity that can improve indigenous resources. All of local potencies done in rural area, not only to get benefit, but also to increase the role of agroindustry. The development of agroindustry is able to increase local food added value, income and opportunities for employment, and so far to get higher regional economic growth. One of theagroindustry in Kokap District , Kulon Progo is ”Sumber Rejeki”, a group of farmers that produce granulated coconut palm sugar.